"The Need for Private Sector Participation In Providing Public Projects in the Kingdom of Saudi Arabia" - Al-Sharif, Faisal; Al-Omar, Ibtisam (The Arab Journal of Administration, 2022)
Many countries around the world have been interested in involving the private sector in the provision of development projects, for a variety of reasons, as the private sector is given a greater role as the most capable and efficient in managing economic activity, with high decision-making freedom, great initiative, creativity and risk-taking in the investment process. On the other hand, public sector investments are not primarily for profit, as much as for the social role of the State, while the private sector seeks to make a profit, and in order to do so always keep innovating and creating in order to maintain its high competitiveness to remain in the market. This study focuses on analysing the nature of the relationship between the public and private sectors in the provision of projects in Saudi Arabia, and the need for this, as well as clarifying the constraints of this type of contracts, and the requirements of successful public-private partnership, with the aim of clarifying and crystallizing the requirements and foundations of the real public-private partnership in the development of economic policies in order to promote the Saudi economy and achieve the desired economic development in the Kingdom’s vision 2030. The descriptive research approach was applied to a sample of public, private and third sector (charitable) employees in an easy manner, The research concluded that there was a need for the serious application of public-private partnership, in order to increase population growth rates, to improve the quality of the services provided, and to address routine procedures that hindered the partnership process. In addition to providing legal and regulatory frameworks that help provide an encouraging, stimulating and reassuring working environment for the private sector to apply for this type of project contract. The study therefore recommends the adoption of this type of contract in the provision of public service projects.